2021
DOI: 10.29333/iejme/11003
|View full text |Cite
|
Sign up to set email alerts
|

Learners’ Critical Thinking About Learning Mathematics

Abstract: Developing critical thinking practices among young learners through mathematics education is a topic of attention for mathematics education research community. Learners' critical thinking concerning cognitive and social aspects of their mathematics education have been explored in several research studies. However, learners' critical thinking concerning their personal beliefs about their mathematics learning process have not received much consideration. In this paper, learners' practice with thinking critically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
1
9
0
6
Order By: Relevance
“…This is a limitation of the study since there is no qualitative data to delve into the findings obtained. Studies on literature review have found that HOTS in Mathematics is indeed valid, but there needs to be more studies on the usefulness of HOTS in Mathematics from pupils' perspective (Anggraini et al, 2019;Sachdeva & Eggen, 2021). Therefore, the findings of this study provide statistical data on the level of pupils' belief towards HOTS in Mathematics to validate the qualitative findings of previous studies.…”
Section: Discussionsupporting
confidence: 63%
“…This is a limitation of the study since there is no qualitative data to delve into the findings obtained. Studies on literature review have found that HOTS in Mathematics is indeed valid, but there needs to be more studies on the usefulness of HOTS in Mathematics from pupils' perspective (Anggraini et al, 2019;Sachdeva & Eggen, 2021). Therefore, the findings of this study provide statistical data on the level of pupils' belief towards HOTS in Mathematics to validate the qualitative findings of previous studies.…”
Section: Discussionsupporting
confidence: 63%
“…High early math ability is essential for students to develop critical thinking skills based on interpretation indicators (Sutama et al, 2022). In fact, students rarely think critically and have inconsistent beliefs about mathematics and the learning process (Sachdeva & Eggen, 2021). Teachers must plan the right strategy so that evaluations using HOTS questions can be carried out correctly.…”
Section: Measure the Quality Of The Learning Environmentmentioning
confidence: 99%
“…Pelajaran matematika yang siswa dapatkan di sekolah menjadi latihan rutin yang dapat mengasah daya kritis mereka. Argumen tersebut dipertegas oleh Muhammad & Yolanda (2022); Sachdeva & Eggen (2021) yang menyatakan bahwa matematika merupakan salah satu aspek penting sebagai mata pelajaran pada berbagai tingkat Pendidikan di seluruh dunia. Pendidikan matematika memiliki peran vital dalam mendidik anak-anak untuk menjadi makhluk berpikir kritis, bertanggung jawab dan kooperatif bertindak dalam masyarakat.…”
Section: Pendahuluanunclassified